Risk Stratification and Anticoagulation in Multiple Myeloma: Tailoring Venous Thromboembolism Prevention and Treatment - Tiwari, Bishal; Sapkota, Samita (Nepalese Journal of Cancer, 2025)
Purpose: Venous thromboembolism (VTE) is a serious complication for patients with multiple myeloma (MM), particularly those undergoing treatment with immunomodulatory drugs (IMiDs). This review aims to explore personalized strategies for managing VTE in MM, with a emphasis on risk stratification methods, emerging biomarkers, and advancements in therapeutic approaches to improve patient care. Design: A thorough review of contemporary evidence was performed to assess the underlying pathophysiology, risk assessment tools, and therapeutic strategies for VTE in MM. Guidelines and multidisciplinary care practices were evaluated to identify shortcomings and propose individualized interventions. Results: MM is associated with a substantially increased risk of VTE, particularly during the initial six months of diagnosis, driven by disease and treatment factors. Risk assessment models (RAMs) like the SAVED and IMPEDE VTE scores have been instrumental in identifying high-risk patients. For instance, the IMPEDE score, validated in multiple cohorts, demonstrates superior predictive capacity, achieving a C-statistic of 0.74 and outperforming traditional tools like the Padua score (AUC: 0.722 vs. 0.591). Moreover, biomarkers such as elevated D-dimer levels and tissue factor activity enhance the precision of VTE risk assessment. Emerging evidence highlights the integration of genetic and acquired thrombophilia markers in VTE management. Hereditary mutations (e.g., Factor V Leiden, prothrombin G20210A) and acquired factors (e.g., dexamethasone use, immobility) significantly contribute to VTE risk. Pharmacological thromboprophylaxis tailored to individual risk profiles remains the cornerstone of VTE prevention. Direct oral anticoagulants (DOACs) offer comparable efficacy to aspirin and low molecular weight heparin (LMWH), with a favorable safety profile, particularly in patients with renal impairment or cancer. However, their cost and limited access in certain regions pose challenges. Conclusion: Effective VTE management in MM demands a multidisciplinary, precision-focused approach. Although risk assessment tools have improved, further refinements are needed to overcome their limitations. Incorporating genetic and acquired thrombophilia markers with evidence-based prophylaxis, especially using DOACs, is a promising avenue for improving care. Future research should emphasize large-scale trials and real-world validation to better mitigate VTE risk and enhance survival in MM.